Ironi Kebijakan Penanaman Modal Asing Yang Tak Kunjung Mendistribusikan Kesejahteraan Sosial - Rochman, Arif; Suardi, Ilham; Habeahan, Rasman (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The foreign investment (PMA) strategy in Indonesia necessitates a thorough overhaul, as the 'top-down' method employed for approximately 64 years has failed to significantly enhance the social welfare of small company operators (MSMEs-K). To date, the PMA policy has been formulated by the Indonesian Government via directives including Presidential rules, Ministerial Decrees, and rules from the Investment Coordinating Board (BKPM), excluding the participation of local players such as Apindo, Kadin, and MSMEs-K. To enhance the inclusivity of the PMA policy, a 'bottom-up' approach is required that incorporates the aspirations of MSMEs-K, is presented via the Regional Investment Board, and is processed incrementally up to BKPM and the Coordinating Ministry for Economic Affairs before presidential ratification. This strategy aims to promote the realisation of substantive-distributive justice, enabling MSMEs-K to experience the advantages of the PMA policy directly. Conversely, the procedural-formal justice model, which solely emphasises formal legal elements, has demonstrated ineffectiveness in allocating welfare to domestic enterprises. The Indonesian government must adopt the principle of distributive fairness, particularly in allocating non-renewable natural resources and budgetary provisions, prioritising local enterprises, especially MSMEs. Keywords: Irony; PMA Policy; Social Welfare Abstrak:Strategi penanaman modal asing (PMA) di Indonesia memerlukan perombakan menyeluruh, karena metode 'top-down' yang diterapkan selama kurang lebih 64 tahun belum mampu meningkatkan kesejahteraan sosial pelaku usaha kecil (UMKM-K) secara signifikan. Selama ini, kebijakan PMA telah dirumuskan oleh Pemerintah Indonesia melalui berbagai arahan, termasuk peraturan Presiden, Keputusan Menteri, dan peraturan dari Badan Koordinasi Penanaman Modal (BKPM), dengan mengesampingkan partisipasi pelaku lokal seperti Apindo, Kadin, dan UMKM-K. Untuk meningkatkan inklusivitas kebijakan PMA, diperlukan pendekatan 'bottom-up' yang menampung aspirasi UMKM-K, disampaikan melalui Badan Penanaman Modal Daerah, dan diproses secara bertahap hingga ke BKPM dan Kementerian Koordinator Bidang Perekonomian sebelum disahkan oleh presiden. Strategi ini bertujuan untuk mendorong terwujudnya keadilan substantif-distributif, sehingga UMKM-K dapat merasakan langsung manfaat kebijakan PMA. Sebaliknya, model keadilan formal-prosedural yang hanya menekankan unsur legal formal telah menunjukkan ketidakefektifan dalam mengalokasikan kesejahteraan kepada perusahaan domestik. Pemerintah Indonesia harus mengadopsi prinsip keadilan distributif, khususnya dalam alokasi sumber daya alam tak terbarukan dan penyediaan anggaran, dengan mengutamakan perusahaan lokal, khususnya UMKM.Kata Kunci : Ironi; Kebijakan PMA; Kesejahteraan Sosial